Liminal and Limioid in Dubravka Ugrešić’s Writing - Ryznar, Anera (Poznańskie Studia Slawistyczne, 2025)
The experience of borderlines, displacement, and non-belonging has fundamentally defined Dubravka Ugrešić’s writing, as well as her personal biography. Initially as an exile, an outcast from national culture, and later as a transnational author and intellectual, she was marked by a position of permanent liminality, existing betwixt and between (Turner) rigid national, social and political structures. The experience of liminality is also embodied in her writing, primarily in the exploration of the topic of exile in the novels The Museum of Unconditional Surrender and The Ministry of Pain. In her later novels the liminal gives way to the liminoid, understood as a particular regime of writing characterized by playfulness, performativity, subversion but also a utopian sense of literary communitas. This paper outlines this shift and demonstrates, using the novel Fox (2017) as an example, how the concepts of the liminal and the liminoidcan contribute to a critical reading of Ugrešić’s fiction.